2021
DOI: 10.1172/jci.insight.145761
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of type I interferon signaling in intrahepatically primed CD8+ T cells promotes functional differentiation

Abstract: Hepatitis B virus–specific (HBV-specific) CD8 + T cells fail to acquire effector functions after priming in the liver, but the molecular basis for the dysfunction is poorly understood. By comparing the gene expression profile of intrahepatically primed, dysfunctional HBV-specific CD8 + T cells with that of systemically primed, functional effector counterparts, we found that the expression of interferon-stimulated genes (ISGs) is selectively suppressed in the dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Poignancy induction of type I interferon (IFN-Is) in the liver also promoted the functional differentiation of intrahepatic perfusion of HBV-specific CD8 + T cells while restoring ISGs expression in T cells, suggesting that robust induction of intrahepatic IFN-Is may be therapeutic for CHB. 20 Prospective studies confirmed that increased frequency of HBV-specific functional CD8 + T cells in NAs discontinuation patients was associated with continued viral control after treatment. Although HBV-specific CD4 + T-cell response is observed with a similar trend, without statistical significance.…”
Section: Virus -S Pecific Cd8 + T Cell S During Hbv Infec Ti Onmentioning
confidence: 88%
See 1 more Smart Citation
“…Poignancy induction of type I interferon (IFN-Is) in the liver also promoted the functional differentiation of intrahepatic perfusion of HBV-specific CD8 + T cells while restoring ISGs expression in T cells, suggesting that robust induction of intrahepatic IFN-Is may be therapeutic for CHB. 20 Prospective studies confirmed that increased frequency of HBV-specific functional CD8 + T cells in NAs discontinuation patients was associated with continued viral control after treatment. Although HBV-specific CD4 + T-cell response is observed with a similar trend, without statistical significance.…”
Section: Virus -S Pecific Cd8 + T Cell S During Hbv Infec Ti Onmentioning
confidence: 88%
“…Moreover, the expression of interferon stimulator genes (ISGs) was reported to be associated with selective inhibition of some special functions of CD8 + T cells. Poignancy induction of type I interferon (IFN‐Is) in the liver also promoted the functional differentiation of intrahepatic perfusion of HBV‐specific CD8 + T cells while restoring ISGs expression in T cells, suggesting that robust induction of intrahepatic IFN‐Is may be therapeutic for CHB 20 . Prospective studies confirmed that increased frequency of HBV‐specific functional CD8 + T cells in NAs discontinuation patients was associated with continued viral control after treatment.…”
Section: Virus‐specific Cd8+ T Cells During Hbv Infectionmentioning
confidence: 99%
“…In stark contrast to exhausted CD8+ T cells during LCMV infection, genes related to IFN-I signaling activation were downregulated in intrahepatically primed T cells. Importantly, strong stimulation of IFN-I signaling in the liver enhanced T cell responses (82), suggesting that IFN-Is indeed provide the third signal (signal 3) that complements the TCR signal (signal 1) and co-stimulatory signal (signal 2). It should be noted, however, that the same IFN-I signaling could suppress HBV-specific CD8+ T cell responses by reducing antigen expression levels during the early phase of T cell priming (67), a phenomenon recently highlighted in the development of RNA vaccines (83).…”
Section: Intrahepatic Antigen Recognitionmentioning
confidence: 99%
“…Because HBcAg cannot be secreted into circulation, these findings again clearly indicate that expression of viral antigen in hepatocytes is tolerogenic due to the lack of sufficient costimulatory signals and reduction of HBcAg expression in hepatocytes by more than 10 folds cannot prevent the induction of CD8+ T cell tolerance. However, it was found that treatment of HBV transgenic mice with type I IFN or IL-2 can rescue, at least in part, the development of the adoptively transferred HBV-specific naïve CD8+ T cells to functional effectors CTLs (50,55). These findings imply that IFN-α or pattern recognition receptor (PRR) agonist therapy of CHB may activate host antiviral immune response via partially rescuing the functional development of hepatocyte-primed CTLs (Fig.…”
Section: Effects Of Reducing Intrahepatic Viral Protein Expression And/or Circulating Hbsag On Antiviral Immune Responses In Mouse Modelsmentioning
confidence: 99%